The Interplay of Non-Verbal Intelligence and Cognitive Functions in Understanding Emotions in Preschool Children - Charkhabi M; Gavrilova M; Tarasova K; Chichinina E; Dutheil F (Psychology Research and Behavior Management, 2025)
Morteza Charkhabi,1,2 Margarita Gavrilova,3 Kristina Tarasova,3 Elena Chichinina,3 Frederic Dutheil4 1Laboratory of Child Psychology and Digital Socialization, Federal Scientific Center for Psychological and Multidisciplinary Research, Moscow, Russia; 2Department of Educational Programs, HSE University, Moscow, Russia; 3Faculty of Psychology, Department of Psychology of Education and Pedagogy, Lomonosov Moscow State University, Moscow, Russia; 4Physiological and Psychosocial Stress, CNRS, LaPSCo, Universite Clermont Auvergne, CHU Clermont-Ferrand, Clermont-Ferrand, FranceCorrespondence: Morteza Charkhabi, Federal Scientific Center for Psychological and Multidisciplinary Research, Moscow, Russia, Tel +7 9104793008, Email mortezacharkhabi@yahoo.comObjective: Emotions are known to play a vital role in the lives of children; however, not all children possess an equal understanding of emotions. This suggests the influence of cognitive abilities and functions on the development of emotion understanding during different developmental phases. This study aims to explore the link between non-verbal intelligence and emotion understanding in children. Also, it examines a mediation model to assess the extent to which cognitive functions mediate this link. Finally, it aims to compare the strength of mediation paths between boys and girls through testing a moderated mediation model.Methods: To test the research hypotheses, a sample of 272 children (M = 63.40 months, SD = 3.74) including 81 boys and 138 girls was recruited. The parents of the remaining 53 children chose not to specify their children’s gender. Participants responded to scales on non-verbal intelligence, executive cognitive functions and emotion understanding.Results: The results suggested that there is a statistically positive relationship between non-verbal intelligence and emotion understanding. Also, the executive cognitive functions were positively associated with both non-verbal intelligence and emotion understanding. The results of multiple mediation analysis revealed that only the inhibition mediated the link between non-verbal intelligence and emotion understanding.Conclusion: These findings suggest that not all executive cognitive functions can explain the underlying mechanism between non-verbal intelligence and emotion understanding, however, inhibition emerged as the stronger mediator in this relationship.Keywords: non-verbal intelligence, cognitive functions, emotion understanding, preschool children